Self-care and accident with biological waste: Grounded Theory - Camargo, Tatiana Braga; Lacerda, Maria Ribeiro; Sarquis, Leila Maria Mansano (Online Brazilian Journal of Nursing, 2010)
Work settings have demanded more and more that workers take care of themselves in order to avoid burnout. In the health area, the professionals who take care of other human beings sometimes forget about themselves and suffer the harmful consequences, among them, work accident with biological hazard. Thus, it aims to identify the factors that foster health workers’ self-care among those who suffered accident with biological waste. This article is part of a dissertation which uses the grounded theory as a methodological landmark, trying to grasp the whole of a phenomenon which portrays the experience of a given social group. The research study has three sampling groups totaling eleven subjects. The first group takes up health workers who had accident with biological waste and ended surveillance, the second one entails the ones who quit surveillance and the third one with professionals who render care to those who had accidents. Data collection was carried out by means of semi-structured interviews between December/2008 and August/2009. Among the themes, categories, sub-categories and components evolved in the dissertation, it was chosen to explicit in this work the category “Perceiving the factors that collaborate in the care of oneself” which comprises the following sub-categories: “Cutting down  accident hazards”, “Facilitating the use of Standard Prevention”, “Setting up Scientific Knowledge Influences”, “Increasing the number of surveillance compliance”. “Being aware”, and “Fearing”. It is necessary to work with these professionals in order to potentialize these factors that help them care of themselves so that attention towards them be increased and brings about beneficial consequences to the health of those individuals who take care of other human beings.